Malignant ventricular arrhythmias in patients with implantable cardioverter-defibrillators: electrical signals which are predictors of recurrence - Ailema A. Alemán-Fernández; Margarita Dorantes-Sánchez; Jesús Castro Hevia; Lisbeth González González; Yoel Coto Hernández; Marcos A. Rodríguez García (CorSalud, 2017)
Introduction: There is a growing number of patients with implantable cardioverter-defibrillators. Recurrences are frequent and electrical shocks are the main factor affecting the quality of life. Objective: To identify the electrocardiographic predictors of the recurrence of malignant ventricular arrhythmias in these patients. Method: From a universe of 76 patients, who had undergone cardioverter-defibrillator implantation, 46 patients were selected and two groups were formed. Group A consisted of 27 patients with at least one episode of malignant ventricular arrhythmias after device implantation; and group B consisted of 19 subjects without recurrences. Measurements (prolonged QTc, abnormal QT dispersion, Tpeak-Tend interval and its abnormal dispersion) were averaged over three consecutive heartbeats in each lead, manually, by two independent observers. Results: In group A, there was a predominance of structural heart disease and an ejection fraction less than 35%. The fragmentation of the QRS complex, bimodal T wave and early repolarization pattern were also present. There were significant differences in the mean values of the QT interval (428 vs. 390 ms), p=0.004; the corrected QT (476 vs. 436 ms), p=0.011; and Tpeak-Tend interval (108 vs. 87 ms), p=0.006. There were no significant differences in QT dispersion (51 vs. 48 ms), the Tpeak-Tend dispersion (35 vs. 27 ms), or QRS duration (121 vs. 105 ms). Conclusions: QT, QTc and Tpeak-Tend intervals are electrocardiographic predictors of the recurrence of ventricular arrhythmias in patients with implantable cardioverter-defibrillators.